Faktor-faktor yang Mempengaruhi Keputusan Orang Tua Untuk Memberikan Vaksinasi Covid-19 pada Anak - Rahmah Hida Nurrizka; Moh. Irvan; Vernanda Eka Hardianto (LPPM Hang Tuah Pekanbaru, 2023)
The Covid-19 vaccination policy for children caused a different response in the community, especially from parents. There are still parents who decide not to vaccinate their children. This study aims to look at the factors that influence the decision of parents to give Covid-19 vaccinations to their children. Some of the independent variables in this study were the children's characteristics, parent characteristics, the history of Covid-19 sufferers in the family, and the history of Covid-19 vaccination in relatives' children. This is a cross-sectional survey study with a sample of 280 parents with children aged 6-11 years in Greater Jakarta. The results showed there were still many respondents who said they were afraid of the side effects of the covid-19 vaccination in children (39.4%), did not know the directions for the vaccine and did not know that the covid-19 vaccination could be given to children (15.2%) and still have doubts about the covid-19 vaccination in children (6.1%). The dominant variable that influences parents' decisions in giving vaccinations to children is the children's age (p-value: 0,001, odds ratio: 1,677, confidence interval: 1,252-2,246), number of children (p-value: 0,013 odds ratio: 0,304, confidence interval: 0,070-1,445) and the history of Covid-19 vaccination in relatives' children (p-value: 0,000, odds ratio: 4,881, confidence interval: 2,175-10,954). This study concludes that there are doubts and obstacles for parents in making decisions to give covid-19 vaccinations to their children. To make a positive response from parents to the covid-19 vaccination policy, good information and examples of the covid-19 vaccination policy for children are needed.